Analisis Kejadian ISPA Pada Balita Di Wilayah Kerja Puskesmas Pelambuan Kota Banjarmasin Tahun 2016 - Agus Jalpi (Jurnal Kesehatan Indonesia, 2017)
Tract disease (infection of the respiratory tract acute) covers acute infection the respiratory tract the top and the respiratory tract the bottom. Eradications of tract disease are divided into tract disease non pneumonia, pneumonia, and heavy pneumonia. Based on data from the Public Health Office of Banjarmasin City 2015, are included in the largest disease who figures it happens is relatively very high. In 2015 cases tract age 1 years reached 14.493 patients. 1-4 years of age 35.503 patients and the days of 5 years 53.275 patients. The kind of research used is research observational by using design cross sectional. Population in this research is all the mothers that have toddler who treatment at poly a child at October 2015 affected by tract as many as 280 cases in the work area of Puskesmas Pelambuan Banjarmasin city. The sample as many as 74 respondents, data collection taken a random sampling. The data collection was done by distributing the questionnaire, interviews and direct observation into the homes and see books registers on poly children Puskesmas Pelambuan. Research in test statistically by chi square test on the levels of trust 95 %. The results of research on 74 respondents indicated that there was a correlation of knowledge p-value 0,001, there was a correlation attitude p-value 0,000, and there was a correlation the use of repellent fuel p-value 0,000 with the tract genesis in toddlers in the work area of Puskesmas Pelambuan 2016. Advice for Puskesmas to evaluate policy one program related to the Community Service especially tract program, for respondents are expected to be more for their and cleanliness environment in efforts to prevent tract and to minimize the use of repellent fuel at home